Reprocessable and healable ethylene copolymer/f-rGO nanocomposites crosslinked by Diels-Alder adducts with infrared- and thermo-responsive behavior. (December 2021) - Kang, Kyung Hee; Chang, Young-Wook; Sabzi, Mohammad
Abstract: In this work, multi-stimuli responsive nanocomposites with recyclability and rapid healability features were developed by simultaneous incorporation of thermo-reversible DA bonds and functionalized reduced graphene oxide (f-rGO) into ethylene copolymer (G-PE). Reversible formation-dissociation of DA crosslinks was investigated by FTIR, 1 H NMR, DSC, and solubility test. It was observed that mechanical properties of the matrix were noticeably improved (modulus ca. 220%, tensile strength ca. 308%, and elongation at break ca. 125%) with loading a quite low amount of f-rGO (0.05 wt%). Interestingly, the results revealed the re-workability of the developed materials with no significant differences in their mechanical properties as well as shape memory (SM) effect after two cycle of melt-reprocessing. Besides, nanocomposites showed scratch-healing and excellent shape recovery under direct heating as well as near infrared light (NIR). Highlights: Chemically crosslinked PE copolymer bearing dynamic Diels-Alder bonds was prepared. The crosslinked PE copolymer/f-rGO nanocomposites exhibited heat- and NIR-induced SM behavior. Thermoreversible Diels-Alder bonds provided reprocessable and healable materials.